Construction and Constriction: Filipino/Moro binary in early republican English documents - Mangurun, Mosa-ab Z. (JOALL (Journal of Applied Linguistics and Literature), 2025)
This research addresses the problem of how the Filipino/Moro binaries are represented within select English legal and constitutional documents and related subjective texts during the early Philippine Republican period. Specifically, it is structured to answer the research questions: a) What are the linguistic mechanisms employed in the Philippine early Republican governmental documents that marginalise Moros? and b) How do these documents perpetuate the Filipino/Moro binary? Data are extracted from English legal and constitutional documents from 1935 to 1975 from the government websites, including the Official Gazette of the Philippines (officialgazette.gov.ph) and the Supreme Court E-Library (elibrary.judiciary.gov.ph). Their source texts are objectified (Republic Acts) or subjective (Presidential Speeches). To analyse how these texts constructed and perpetuated marginalisation and oppositional binaries, Foucault’s (1972) framework was employed. Its application here involves a genealogical examination of the archival corpus and selecting texts that explicitly reference the Moro population or their biopolitical and territorial governance. In the genealogical analysis, data are subjected to a coding process and thematic categorisation of the discursive practices. The study elucidates the persistent influence of these discursive formations on the Moros' pursuit of equitable representation within the nation-state’s biopolitical framework. Consequently, the findings entail the necessity for a reconceptualisation of national identity that embraces the multiplicity and diversity of the archipelago's indigenous populations. This study is significant as it sheds light on the complex dynamics of power, knowledge, and identity construction, and their lasting effect on the contemporary political realities of the Bangsamoro Autonomous Region in Muslim Mindanao (BARMM). Understanding these is fundamental to achieving authentic and attainable peace in this volatile region.